Growth hormone‐induced insulin resistance in human subjects involves reduced pyruvate dehydrogenase activity. (22nd November 2013) - Nellemann, B.; Vendelbo, M. H.; Nielsen, T. S.; Bak, A. M.; Høgild, M.; Pedersen, S. B.; Biensø, R. S.; Pilegaard, H.; Møller, N.; Jessen, N.; Jørgensen, J. O. L.
Abstract Aim Insulin resistance induced by growth hormone (GH) is linked to promotion of lipolysis by unknown mechanisms. We hypothesized that suppression of the activity of pyruvate dehydrogenase in the active form (PDHa) underlies GH‐induced insulin resistance similar to what is observed during fasting. Methods Eight healthy male subjects were studied four times in a randomized, single‐blinded parallel design: Control, GH, Fasting (36 h) and GH + Fasting. GH (30 ng × kg−1 × min−1) or saline was infused throughout the metabolic study day. Substrate metabolism and insulin sensitivity were assessed by indirect calorimetry and isotopically determined rates of glucose turnover before and after a hyperinsulinemic euglycemic clamp. PDHa activity, PDH‐E1α phosphorylation, PDK4 expression and activation of insulin signalling proteins were assessed in skeletal muscle. Results Both fasting and GH promoted lipolysis, which was associated with ≈50% reduction in insulin sensitivity compared with the control day. PDHa activity was significantly reduced by GH as well as fasting. This was associated with increased inhibitory PDH‐E1α phosphorylation on site 1 (Ser293) and 2 (Ser300) and up‐regulation of PDK4 mRNA, while canonical insulin signalling to glucose transport was unaffected. Conclusion Competition between intermediates of glucose and fatty acids seems to play a causal role in insulin resistance induced by GH in human subjects.